1997
DOI: 10.1111/j.1365-3156.1997.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of visceral leishmaniasis by the polymerase chain reaction using blood, bone marrow and lymph node samples from patients from the Sudan

Abstract: SummaryWe have evaluated the sensitivity of the polymerase chain reaction (PCR) as a diagnostic tool for Leishmania donouani using blood, bone marrow and lymph node samples from Sudanese patients with a confirmed infection. Forty patients were diagnosed by microscopic examination of bone marrow or lymph node samples. The PCR was able to detect parasite DNA in 3 7 out of 40 blood samples. In bone marrow and lymph node samples, the PCR was able to detect parasite DNA in all 7 and 6 samples, respectively. We sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…For diagnosis of VL, bone marrow and lymph node aspirates as well as blood samples have been evaluated. Bone marrow aspirates from parasitologically confirmed VL patients were always PCR positive in several studies (Mathis & Deplazes 1995; Andresen et al . 1997; Osman et al .…”
Section: Diagnosismentioning
confidence: 94%
See 1 more Smart Citation
“…For diagnosis of VL, bone marrow and lymph node aspirates as well as blood samples have been evaluated. Bone marrow aspirates from parasitologically confirmed VL patients were always PCR positive in several studies (Mathis & Deplazes 1995; Andresen et al . 1997; Osman et al .…”
Section: Diagnosismentioning
confidence: 94%
“…1994). In human lymph node aspirates Leishmania DNA was detected by PCR in all six samples in one study (Andresen et al . 1997) and in 33/38 samples in another (Osman et al .…”
Section: Diagnosismentioning
confidence: 99%
“…In our study, PB kDNA-PCR showed a good concordance with the rapid immunochromatographic test (PB-rK39) (0.74, p < 0.001), which is a rapid and highly sensitive technique, so that it has been used as a reference test. Disch et al [9] and Andresen et al [19] obtained sensitivities of 91% (48/53) and 92.5% (37/40) when kDNA-PCR was used to test whole blood from PB samples of patients with VL, confirmed by clinical and microscopic examination of BM or lymph node samples. Fraga et al [20] evaluated the effectiveness of a kDNA-PCR in PB and found a very good sensitivity (43/45; 95.6%), which was higher than that found in BM samples: kDNA (41/45; 91.1%); microscopic examination of smear (36/45; 80%); and culture (12/45; 26.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The technique was tested with VL samples of different clinical materials (peripheral blood, aspirates from lymph nodes and bone marrow); with samples taken at different stages of the disease from the endemic area in eastern Sudan ( Osman et al . 1997a , b, 1998b) and in a hospital‐based study ( Andresen et al . 1997 ).…”
Section: Diagnosismentioning
confidence: 99%